Energy use and rural poverty: empirical evidence from potato farmers in northern China - Li, Zihan; Gong, Yazhen; Chen, Kevin Z. (Emerald Publishing Limited, 2019)
Rising energy expenditures due to more intensive use of energy in modern agriculture and increasing energy prices may affect rural households’ agricultural incomes, particularly the incomes of the rural poor in developing countries. However, the exact link between energy costs and income among the rural poor needs further empirical investigation. The purpose of this paper is to develop a deeper understanding of the relationship between energy use and family income, using household-level panel data collected from 500 potato farmers in a poor region of Northern China, where eliminating poverty by 2020 is now the top government priority.The paper uses household survey data collected from six counties in a poor region in northern China in 2013 to measure the relationship between energy cost and family income. A fixed effect model is employed to estimate the relationship.The findings indicate that potatoes play an important role in the surveyed families’ incomes, and that the energy costs of potato production have a significant negative relationship with family income. However, this negative relationship is only significant for farmers with low economic standing, such as those living below or just above the poverty line. The negative relationship between energy costs and family income is only significant for those cultivating a certain size of potato-sown area; it is insignificant for those cultivating smaller areas.These findings indicate that, in general, reducing energy costs helps the poor increase their income but is not necessarily helpful to those with high economic standing or a relatively small potato-sown area. If rural development policies are to support poverty reduction and energy savings (at least in major potato production regions), interventions aimed at energy cost reduction may be effective only for the poor whose family income depends, to a relatively high degree, on potato production.